A PRAGMATIC ANALYSIS OF POSITIVE POLITENESS STRATEGIES ON TED TALK VIDEO BY EDDY ZHONG - Ike Idriani Saragih; Nur Azizah; Ita Rahayu; Evi Zulida; Chairuddin Chairuddin; Makhroji Makhroji (Journal of Education, Linguistics, Literature and Language Teaching, 2019)
Politeness phenomena do not only occur in daily conversations, but also in the speeches delivered by the speakers. The speech on TED Talk video by Eddy Zhong entitled “How School Makes Kids Less Intelligent” is one of the interesting subjects to be analyzed in terms of positive politeness strategies. This speech explained the speaker's experience during school and how he had built his business in the field of technology since he was 16 years old. In addition, they also conducted experiments and compared the thinking between children who had just entered elementary school and teenagers in senior high school, and the results reinforce his statement about the title he brought Thus, the aims of this research are (1) to find the positive politeness strategies in the speech on TED Talk video by Eddy Zhong entitled “How School Makes Kids Less Intelligent” (2) to analyze the positive politeness strategies in the speech on TED Talk video by Eddy Zhong entitled “How School Makes Kids Less Intelligent”. This research employed descriptive qualitative research. The data were in the form of statements and sentences uttered by Eddy Zhong on TED Talk video entitled “How School Makes Kids Less Intelligent”. The main instrument of the study was the researchers themselves and the secondary instrument was a data sheet. The data were analyzed with the use of a referential method. Such a method analyzes the data in reference to the theory employed in this study. The results of the research show that all of the fifteen strategies of positive politeness appear, except the strategies of (Including both speaker and hearer in the activity; Asserting reciprocal exchange or tit for tat; and Giving gifts to hearer (goods, sympathy, understanding, cooperation)). As it is drawn in Table 1, there are 32 occurrences of positive politeness strategies in a speech on TED Talk video by Eddy Zhong entitled “How School Makes Kids Less Intelligent”. In the highest rank is (Joking to put the hearer at ease) which gets a frequency of 9. The second rank is (using in-group identity markers in speech; and intensifying interest to the hearer in the speaker’s contribution) with 6 data each of these data. The third rank is the strategies of (seeking agreement in safe topics; being optimistic that the hearer wants what the speaker wants; and giving or asking for reasons) which occur in 3 data each of these data. Meanwhile, the last rank is covered by the strategies which have the occurrence 1 data, those are the strategies of (exaggerating (interest, approval, sympathy with hearer); and presupposing, raising, asserting common ground).